Electronic Structure Trends in N‐Heterocyclic Carbenes (NHCs) with Varying Number of Nitrogen Atoms and NHCTransition‐Metal Bond Properties. Issue 38 (16th August 2013) - Bernhammer, Jan C.; Frison, Gilles; Huynh, Han Vinh
Abstract Carbenes derived from five‐membered heterocycles with different numbers of nitrogen atoms ranging from two to four lead formally either to normal N‐heterocyclic or mesoionic carbenes with, in some cases, the same skeletal structure. The electronic structures of fourteen of these compounds were examined by means of DFT calculations at the B3LYP/aug‐cc‐pVTZ level. The examined parameters include the energies of the σ‐lone pair at Ccarbene and the π‐HOMO of the protonated form, which are correlated to the first and second proton affinities. The singlet–triplet energy gap was used as a measure of the stability of the N‐heterocyclic carbene (NHC) towards dimerisation. Natural population analysis provided insight into the variation of the pπ population and the natural charge at Ccarbene with NHC structure. Additionally, the transition metalNHC bond in L‐AuCl and L‐TiCl4 and the nature of the orbital interactions between the NHC and the transition‐metal fragment were analysed in detail by the extended transition state–natural orbitals for chemical valence (ETS–NOCV) approach at the BP86/TZ2P level. Similarities and differences between the NHCgold and the NHCtitanium bond are discussed, and trends in key bonding properties can be traced back to the variation of the electronic parameters of the NHC.